THE INFLUENCE OF IMPLEMENTING A WETLAND-BASED SCCRT STEAM AUGMENTED REALITY AI REACTION RATE E-MODULE ON THE LEARNING OUTCOMES OF GRADE XI STUDENTS AT SMA NEGERI 2 PALANGKA RAYA - Nopriawan Berkat Asi; Triliyansi; Rini Sundari; Nurul Hayati (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2026)
21st-century chemistry education requires the integration of digital technology and innovative pedagogical approaches to improve student learning outcomes, particularly in abstract topics such as reaction rates. This study aims to analyze the influence of implementing a reaction rate e-module based on Structured, Collaborative, Creative, and Reflective Thinking (SCCrT) and STEAM, integrated with Augmented Reality (AR), Artificial Intelligence (AI), and a wetland context, on the learning outcomes of Grade XI students at SMA Negeri 2 Palangka Raya. The research employed a quantitative approach with a quasi-experimental nonequivalent control group design. The research sample consisted of 63 students divided into an experimental class and a control class. Data were collected through learning outcome tests and a 1–4 Likert scale questionnaire measuring citizenship, collaboration, and communication. Data analysis was performed using SPSS and SmartPLS. The results showed that the experimental class achieved a higher increase in learning outcomes than the control class, with an N-Gain score of 0.68 and an effect size of 0.92 (large category). The SEM-PLS test results indicated that the e-module had a significant effect on learning outcomes (β = 0.52; p < 0.001), both directly and through the mediation of social constructs. These findings confirm that the integration of SCCrT, STEAM, AR, AI, and the wetland context is capable of creating interactive, contextual, and effective chemistry learning to improve students' learning outcomes and social skills.